Rising cereal prices in Ethiopia: An assessment and possible contributing factors - Minten, Bart; Dorosh, Paul A. (International Food Policy Research Institute, 2019)
Nominal cereal prices in Ethiopia in July 2019 were significantly higher than the year before – maize prices had risen by 32 percent; sorghum by 39 percent; teff by 35 percent; and wheat by 2 percent. Moreover, there is anecdotal evidence that nominal cereal prices have increased rapidly since. A number of factors help explain this pattern: Overall inflation has been high both for food and non-food items. This general high inflation is linked to macro factors related to broad money and credit growth; overall changes in prices for inputs, labor, and transport have important impacts on production costs for agricultural products, thereby putting upward pressure on prices. However, controlling for inflation, real prices are close to average real prices over the last ten years, indicating little change in supply relative to demand; seasonality is important in Ethiopian cereal markets, with mostly higher prices in August and September, just before the new Meher harvest comes in. The current (September 2019) high prices for food are partly a seasonal phenomenon; there are no signs of increased real marketing costs. Nonetheless, given their importance for food security, close monitoring and assessments of the functioning of Ethiopia’s food markets remains necessary.